Diseases of tropical pasture plants in sub-Saharan Africa - Mohamed-Saleem, M.A.; Berhe, Kahsay (CAB International, 1994)
This chapter summarises the diseases of important grasses, legumes, forage crops and fodder trees in sub-Saharan Africa which have been recorded, mainly by research workers during the implementation of trials in sown pastures and rangeland. Diseases of legumes are discussed for species of acacia, albizia, centrosema, Gliricidia sepium, Lablab purpureus, Leucaena leucocephala, Macroptilium atropurpureum, Macrotyloma axillare, Neonotonia wightii, stylosanthes, trifolium and miscellaneous species. Diseases of grasses is discussed with particular reference to andropogon, brachiaria, Cenhrus ciliaris, Chloris gayana, cynodon, digitaria, hyparrhenia, Melinis minutiflora, panicum, paspalum, Pennisetum purpureum, Setaria sphacelata and Sorghum arundinaceum var. sudanense.